faktor risiko FAKTOR RISIKO ERGONOMI TERJADINYA KELUHAN MUSCULOSKELETAL PADA PEKERJA DI INDUSRTI - Erina, Rista (Jurnal Kesehatan Samodra Ilmu (JKSI), 2023)
Studies from the Ministry of Health in the profile of health problems in Indonesia show that about 40.59% of illnesses suffered by workers are work-related. Health problems experienced by workers based on research conducted on 9,482 workers in 12 districts/ cities in Indonesia showed the highest number, namely musculoskeletal disorders (16%) followed by cardiovascular disorders (8%), nervous disorders (596). respiratory disorders (3%), and ENT disorders (1.5%) (Sekaaram & Ani, 2017). This research method uses a Literature Review or literature review with a Systematic Literature Review approach by searching for articles through search engines such as Google Scholar. The keywords used in the search for articles in research on ergonomic risk, age, gender, MSDs, NBM.in selecting articles using inclusion criteria and journal analysis. The results of the literature review on age obtained 5 journals where 4 of these journals had a relationship and I of these journals had no relationship between age and musculoskeletal complaints in industrial workers. Meanwhile, the results of the literature review on gender obtained 5 journals where 2 of these journals had a relationship and 3 of them had no relationship between gender and musculoskeletal complaints in industrial workers. The conclusion states that there is a relationship between age and musculoskeletal complaints, while there is no relationship between gender and musculoskeletal complaints. Suggested it is preferable for women workers aged 30 years to differentiate between working period and working time because women's muscle strength is different from men's muscle strength as well as work methods and work rotation regularly so that skeletal muscle complaints can be minimized.